Out‐Of‐Plane Metal Coordination for a True Solvent‐Free Building with Molecular Bricks: Dodging the Surface Ligand Effect for On‐Surface Vacuum Self‐Assembly. (10th March 2021) - Orbelli Biroli, Alessio; Calloni, Alberto; Bossi, Alberto; Jagadeesh, Madan S.; Albani, Guglielmo; Duò, Lamberto; Ciccacci, Franco; Goldoni, Andrea; Verdini, Alberto; Schio, Luca; Floreano, Luca; Bussetti, Gianlorenzo
Abstract: The desirable self‐assembly (SA) of repeated 2D stacked layers requires a "holistic analysis" of three interconnected components: the electrode, the interface, and the molecular component; among them, the contact interface bears the largest burden responsibilities. Epitaxial growth (EG) of coherent 2D+ n stacked heterojunction by solvent‐free deposition holds great promise, although the feasibility has never been demonstrated given multiple drawbacks (e.g., surface‐ligand effect, SLE). Here, it is demonstrated how a coherent 2D+ n ( n  = 3) layered heterorganic film is grown on an archetypal Fe metal electrode. The groundbreaking achievement is the result of the in‐vacuum integration of: i) chemical decoupling of the basal organic layer (a Zn II ‐tetraphenylporphyrine, ZnTPP) from the metal electrode, ii) 2D‐ordering of the ZnTPP commensurate to the substrate, iii) rigid, stoichiometric, and orthogonally arranged, the molecule‐to‐molecule coupling between ZnTPP and a ditopic linear bridging ligand (i.e., DPNDI) guided by SA coordination chemistry, and iv) sharp (chemical) termination of the layered film. Abstract : In‐vacuum construction of an out‐of‐plane (normal to the surface) self‐assembled heterostructure guided by coordination chemistry. The whole construct, albeit ordered and commensurate, is settled on a pure "physical contact interface" ever realized between a molecule and a metallic surface.